Binary Opposition Between Arrogance and Patience in Owenson’s The Missionary: An Indian Tale - Ammai, Narayan Prasad (Journal of NELTA Surkhet, 2015)
“The Missionary: An Indian Tale” by Sydney Owenson (1811) a remarkable novel written in the backdrop of Spanish-Portuguese conflict in India, a haunting tale of cultural encounter and trans-racial romance set in early colonial India, deals with the theme of binary opposition between arrogance and patience. The Missionary focuses on the binary opposite relationship between Hilarion, a Portuguese missionary to India and Luxima, an Indian prophetess. Hilarion in the novel is presented as a colonizer who seems to be proud on his religion and intends to transform Luxima into Christian from Hindu whereas Luxima’s patience is privileged. Both are aristocratic, devoted to their religions, and biased against other cultures. The primary objective of this study is to analyze how the state of binary opposition between Hilarion’s arrogance and Luxima’s patience exists. The focus of this study is what made Hilarion to be converted in front of Luxima who was supposed to convert her. Owenson is saying that it is the subjectivity of Luxima that gets transferred to Hilarion but not vice versa. By valorizing Luxima’s subjectivity over Hilarion, the writer foregrounds the hidden value of the Hindu culture that gives emphasis not only upon the reason rather puts equal space for emotion. For this purpose the concepts of John Whale and Michael J. Franklin in used as a basic tool of textual analysis to prove its hypothesis. Journal of NELTA Surkhet Vol.4 2014: 98-104